Os professores do 1º ciclo do ensino recorrente: as pessoas e os profissionais - Faca, Maria Madalena Baía Justo Sousa (2006)
In the field of Adult Education, Recurring Teaching is one of the available offers in which the former can take place, being, mainly, in accordance with the Lei de Bases do Sistema Educativo, a second chance opportunity for education offered to those who did not take advantage of it at the right age range or dropped out of school. At the First Cycle of education level, Recurring Teaching encompasses the first four years of school and seeks to ensure to all citizens the right to education, as defined by the Constitution of the Portuguese Republic. This investigation, using strategies of a qualitative nature, sought to identify the main traits of the teachers currently practicing the First Cycle of Recurring Teaching, and from those, extrapolate the profile of these professionals. The subjects of this study are ten teachers, who, during the school year of 2003- 2004, practiced this kind of teaching in the Olhão County. Data was collected through semi-structured interviews, which were done to the subjects, as well as, for effects of contrasting, to the County Coordinator for Recurring Teaching. The interpretative analysis of data showed that, regardless of work experience, training for teaching practice and all the difficulties with which the interviewees were faced, being a teacher of the First Cycle of Recurring Teaching is an extremely rewarding and enriching activity, both in the personal and professional aspects, one in which the interpersonal human relationships take a very relevant meaning, with the creation of bonds between teacher and students that goes well beyond the pedagogical relationship itself. From this study comes, also, the need for having specific training given to future teachers who will work with an adult audience.